2019
DOI: 10.1123/ijspp.2018-0354
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Characteristics and Match Outcome on Technical Errors During Rugby League Match Play

Abstract: Purpose: To explore the relationship between technical errors during rugby league games, match success, and physical characteristics. Methods: A total of 27 semiprofessional rugby league players participated in this study (24.8 [2.5] y, 183.5 [5.3] cm, 97.1 [11.6] kg). Aerobic fitness, strength, and power were assessed prior to the start of the competitive season before technical performance was tracked during 22 competitive fixtures. Attacking errors were determined as any error that occurred in possession of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This method of quantifying match performance is similar to that used previously (25,41). Furthermore, the number of individual errors (e.g., knock on and forward pass), hit up meters (i.e., meters travelled in possession of the ball), and missed tackles were provided by "STATS" (STATS, IL, Chicago) and were considered relative to individual match time because it has been shown that these technical statistics are key performance indicators (12,20).…”
Section: Methodsmentioning
confidence: 99%
“…This method of quantifying match performance is similar to that used previously (25,41). Furthermore, the number of individual errors (e.g., knock on and forward pass), hit up meters (i.e., meters travelled in possession of the ball), and missed tackles were provided by "STATS" (STATS, IL, Chicago) and were considered relative to individual match time because it has been shown that these technical statistics are key performance indicators (12,20).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, elite rugby league players have been shown to focus on different movements and cues during rugby league movement patterns when compared to novices [49]. It has also been reported that the highest error rates occurred when defending the goal line, where the opposition is likely to be more expansive in their play [50]. This research indicates that the ability to tackle effectively is vital for rugby league performance, while suggesting a player's perception and decision-making are also key.…”
Section: Physical and Physiological Qualitiesmentioning
confidence: 70%
“…Previous literature has shown such adaptations to be associated with improvement of individual skills and capacity, such as tackling ability, sprint ability, and decreased likelihood of defensive errors within 20 m of own goal line (5,17,22,37). All of these skills may contribute to findings that have shown these training adaptations to discriminate between skill levels (5,17,22,37). Quantifying and monitoring resistance training loads assist performance staff in interpreting training adaptations that may enhance performance or result in nonfunctional overreaching or overtraining during a training session, a training cycle, and a training year (21).…”
Section: Introductionmentioning
confidence: 99%
“…Strength and conditioning coaches devote a considerable amount of time and effort prescribing and selecting exercises to elicit training adaptations, such as increases in muscle size, strength, and power. Previous literature has shown such adaptations to be associated with improvement of individual skills and capacity, such as tackling ability, sprint ability, and decreased likelihood of defensive errors within 20 m of own goal line (5,17,22,37). All of these skills may contribute to findings that have shown these training adaptations to discriminate between skill levels (5,17,22,37).…”
Section: Introductionmentioning
confidence: 99%